Regional sanctions as peer review: The African Union against Egypt (2013) and Sudan (2019). Issue 4 (September 2021) - Hellquist, Elin
This article offers a novel argument about regional sanctions as in-group peer review, drawing on an analogy from the world of academic publishing. Through their leaning on community-derived authority, equality before the peer, and constructive criticism, regional sanctions have a previously overlooked legitimacy advantage over out-group sanctions used by external actors. The article probes the empirical bearing of this argument for African Union (AU) sanctions against Egypt (2013) and Sudan (2019). Even in these contentious democratic crises, perceptions of sanctions in African media broadly support the theoretical intuition of regional sanctions as a form of peer review. It is, however, far from obvious that peer review leads to successful enforcement of democratic norms beyond urgent crisis. Pragmatic and resolution-oriented, AU sanctions aim at avoiding anarchy rather than at achieving flawless democracy.